Optical laminate and display device

By using an optical laminate with a polarizing film with a high haze and an adhesive layer containing a specific compound in the display device, the challenge of improving contrast in multiple display panel devices is solved, and a higher image display effect is achieved.

CN119805811APending Publication Date: 2025-04-11NITTO DENKO CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411399903.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-10
Filing Date
2024-10-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In display devices using multiple display panels, there is a challenge to improve image display contrast, especially when compared to a single-piece display panel.

Method used

A polarizer containing a polarizing film having a relative position is used, an adhesive layer arranged on both sides of the polarizing film, with a haze of 66% or more, and is composed of a polyvinyl alcohol-based film containing iodine, and contains a compound having a nitroyl radical or a nitrooxy group.

Benefits of technology

With this optical laminate, the characteristics of the display devices of a plurality of display panels are improved, and the contrast ratio of image display is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119805811A_ABST
    Figure CN119805811A_ABST
Patent Text Reader

Abstract

The present application provides an optical laminate using a display device suitable for a plurality of display panels. An optical laminate (60) is provided with: a polarizer (30) including a polarizing film (10) having a first main surface (10a) and a second main surface (10b) facing each other; a first adhesive layer (41) disposed on the first main surface (10a) side of the polarizing film (10); and a second adhesive layer (42) disposed on the second main surface (10b) side of the polarizing film (10). The haze of at least one of the first adhesive layer (41) and the second adhesive layer (42) is 66% or more, and the polarizing film (10) is composed of a polyvinyl alcohol-based film containing iodine and contains a compound having a nitroxyl radical or a nitroxyl group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body and a display device. Background Art

[0002] Depending on the application of display devices represented by liquid crystal display devices, there is a need for further improvement in the contrast of displayed images.

[0003] For example, as a technology for improving the contrast of a liquid crystal display device, a technology for overlapping two display panels and displaying an image on each display panel has been proposed (for example, see Patent Document 1). Specifically, it has been proposed to display a color image on the front side (observer side) of the two display panels arranged in the front and back, and to display a black and white image on the rear side (backlight side) of the display panel, so as to improve the contrast.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2007-310161 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In display devices, optical components such as polarizing components and phase difference components are generally used to realize image display and improve image display performance. However, in display devices using multiple display panels, problems that do not occur in display devices using a single display panel may sometimes occur.

[0009] In view of the above, a main object of the present invention is to provide an optical laminate suitable for a display device using a plurality of display panels.

[0010] Means for solving problems

[0011] 1. An optical laminate according to an embodiment of the present invention comprises: a polarizing plate including a polarizing film having a first main surface and a second main surface opposite to each other; a first adhesive layer arranged on the first main surface side of the polarizing film; and a second adhesive layer arranged on the second main surface side of the polarizing film, the haze of at least one of the first adhesive layer and the second adhesive layer is 66% or more, and the polarizing film is composed of a polyvinyl alcohol-based film containing iodine and contains a compound having a nitroxyl radical or a nitrooxy group.

[0012] 2. In the optical laminate according to item 1 above, the second pressure-sensitive adhesive layer may have a haze of 66% or more.

[0013] 3. The optical laminate according to 2 above may further include a third pressure-sensitive adhesive layer disposed on the second main surface side of the polarizing film.

[0014] 4. The optical layered body according to 2 or 3 above may further include a support disposed on the second main surface side of the polarizing film.

[0015] 5. In the optical layered body according to any one of 1 to 4 above, the content of the compound having a nitroxyl radical or a nitrooxy group in the polarizing film may be 20% by weight or less.

[0016] 6. In the optical layered body according to any one of 1 to 5 above, the content of the iodine in the polarizing film may be 1% by weight or more and 15% by weight or less.

[0017] 7. An optical laminate according to any one of 1 to 6 above, wherein the first adhesive layer can also be formed by an adhesive composition comprising a (meth)acrylic polymer and a cross-linking agent, the cross-linking agent includes an isocyanate cross-linking agent, and the content of the isocyanate cross-linking agent can also be less than 1 part by weight relative to 100 parts by weight of the (meth)acrylic polymer.

[0018] 8. The optical layered body according to item 7 above, wherein the isocyanate crosslinking agent may be a non-aromatic ring system.

[0019] 9. The display device of an embodiment of the present invention is a display device in which a plurality of display panels including a liquid crystal unit are overlapped and arranged, and an image is displayed in each of the above-mentioned display panels, and the display device comprises: a first display panel; a second display panel arranged at a position closer to the observer than the above-mentioned first display panel; and an optical laminate described in any one of 1 to 8 above and arranged between the above-mentioned first display panel and the above-mentioned second display panel, the above-mentioned first adhesive layer of the above-mentioned optical laminate being bonded to the above-mentioned first display panel.

[0020] Effects of the Invention

[0021] According to the optical laminated body of the embodiment of the present invention, the characteristics of a display device using a plurality of display panels can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic cross-sectional view showing a schematic structure of the optical layered body according to the first embodiment of the present invention.

[0023] Figure 2 It is a schematic cross-sectional view showing a schematic structure of an optical layered body according to a second embodiment of the present invention.

[0024] Figure 3This is a schematic cross-sectional view schematically showing a liquid crystal display device according to one embodiment of the present invention.

[0025] Explanation of symbols

[0026] 1 Display device panel

[0027] 10 Polarizing film

[0028] 21 First protective layer

[0029] 22 Second protective layer

[0030] 30 Polarizer

[0031] 41 first adhesive layer

[0032] 42 second adhesive layer

[0033] 43 third adhesive layer

[0034] 50 Support

[0035] 60 optical laminate

[0036] 61 Optical laminate

[0037] 100 1st display panel

[0038] 200 2nd display panel DETAILED DESCRIPTION

[0039] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to these embodiments. In order to make the description clearer, the drawings sometimes schematically show the width, thickness, shape, etc. of each part compared with the embodiments, but this is an example and does not limit the interpretation of the present invention. In addition, for the drawings, the same or equivalent elements are marked with the same symbols, and repeated descriptions are sometimes omitted.

[0040] (Definition of Terms and Symbols)

[0041] The definitions of terms and symbols in this specification are as follows.

[0042] (1) Refractive index (nx, ny, nz)

[0043] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.

[0044] (2) In-plane phase difference (Re)

[0045] "Re(λ)" is the in-plane phase difference measured by light of wavelength λnm at 23°C. For example, "Re(550)" is the in-plane phase difference measured by light of wavelength 550nm at 23°C. When the thickness of the layer (film) is set to d(nm), Re(λ) is calculated by the formula: Re(λ) = (nx-ny)×d.

[0046] (3) Retardation in the thickness direction (Rth)

[0047] "Rth(λ)" is the phase difference in the thickness direction measured by light of wavelength λnm at 23°C. For example, "Rth(550)" is the phase difference in the thickness direction measured by light of wavelength 550nm at 23°C. When the thickness of the layer (film) is set to d(nm), Rth(λ) is calculated by the formula: Rth(λ) = (nx-nz)×d.

[0048] (4) Nz coefficient

[0049] The Nz coefficient is obtained by Nz=Rth / Re.

[0050] (5) Angle

[0051] When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise relative to a reference direction. Therefore, for example, "45°" means ±45°.

[0052] [Optical laminate]

[0053] Figure 1 It is a schematic cross-sectional view showing the general structure of the optical laminate of the first embodiment of the present invention. The optical laminate 60 includes a polarizer 30. The polarizer 30 includes: a polarizing film 10 having a first main surface 10a and a second main surface 10b opposite to each other; a first protective layer 21 arranged on the first main surface 10a side of the polarizing film 10; and a second protective layer 22 arranged on the second main surface 10b side of the polarizing film 10. In addition, the optical laminate 60 includes: a first adhesive layer 41 arranged on the first main surface 10a side of the polarizing film 10; and a second adhesive layer 42 arranged on the second main surface 10b side of the polarizing film 10. The first protective layer 21 can also function as a phase difference layer. In this case, the first protective layer (phase difference layer) 21 can have any suitable optical properties (such as refractive index characteristics, in-plane phase difference, Nz coefficient, photoelastic modulus, etc.).

[0054] Although not shown, the polarizing plate 30 may include an adhesive layer for bonding the protective layer to the polarizing film 10. Figure 1 In the polarizing plate 30 shown in , an adhesive layer may be provided between the polarizing film 10 and the first protective layer 21 , and an adhesive layer may be provided between the polarizing film 10 and the second protective layer 22 .

[0055] The optical laminate 60 includes a support 50 disposed on the second main surface 10b side of the polarizing film 10. A second pressure-sensitive adhesive layer 42 is disposed between the polarizer 30 and the support 50. Specifically, the support 50 is bonded to the polarizer 30 via the second pressure-sensitive adhesive layer 42.

[0056] The optical laminate 60 includes a third adhesive layer 43 disposed on the second main surface 10b side of the polarizing film 10. In the example shown in the figure, the third adhesive layer 43 is provided on the surface of the support 50. The optical laminate 60 is formed so as to be attached to other components through the first adhesive layer 41 and the third adhesive layer 43. For example, the optical laminate 60 is formed so as to be attached to a display panel through the first adhesive layer 41 and the third adhesive layer 43.

[0057] In actual use, release liners (not shown) are attached to the surfaces of the first adhesive layer 41 and the third adhesive layer 43, respectively, and the first adhesive layer 41 and the third adhesive layer 43 can be protected by the release liners. The release liners are temporarily attached to the first adhesive layer 41 and the third adhesive layer 43, for example, until the optical laminate 60 is provided for use. Specifically, the release liners are temporarily attached to the first adhesive layer 41 and the third adhesive layer 43 until the optical laminate 60 is attached to the display panel. As the release liner, a plastic film with a release agent coated on the surface is typically used.

[0058] Figure 2 1 is a schematic cross-sectional view showing the general structure of the optical laminate of the second embodiment of the present invention. In the second embodiment, the optical laminate 61 is different from the first embodiment in that the support 50 and the third adhesive layer 43 are not provided. In the second embodiment, the optical laminate 61 is made to be attached to other components through the second adhesive layer 42 instead of the third adhesive layer 43. Moreover, in actual use, a release liner (not shown) is attached to the surface of the second adhesive layer 42, and the second adhesive layer 42 can be protected by the release liner.

[0059] The haze of at least one of the first adhesive layer 41 and the second adhesive layer 42 is, for example, 66% or more and 99% or less, and preferably 70% or more. The adhesive layer having such a haze can function as, for example, a light diffusion layer.

[0060] The adhesive layer that can satisfy the above-mentioned haze representatively comprises microparticles. As microparticles contained in the adhesive layer, for example, inorganic microparticles that sometimes also have conductivity, crosslinked or uncrosslinked organic microparticles and organosilicon microparticles formed by various polymers such as silicon dioxide, aluminum oxide, titanium dioxide, zirconium oxide, calcium oxide, tin oxide, indium oxide, cadmium oxide, antimony oxide, etc. can be listed. Among them, preferably use spherical silicon dioxide particles, spherical glass beads and spherical organosilicon particles. These microparticles can be used alone, or two or more can be used in combination.

[0061] The particle size of the microparticles can be designed to be smaller than the thickness of the adhesive layer (light diffusion layer). If the particle size of the microparticles is larger than the thickness of the adhesive layer, unevenness can be generated on the surface of the adhesive layer. The particle size of the microparticles is preferably 1 to 50 μm, more preferably 2 to 10 μm.

[0062] The content of the fine particles in the adhesive layer is, for example, 1% to 50% by weight, and preferably 1% to 10% by weight. In one embodiment, the haze of the adhesive layer can be controlled by adjusting the content of the fine particles in the adhesive layer.

[0063] <Polarizing Film>

[0064] The polarizing film is typically a film containing a dichroic substance (typically iodine). For example, the polarizing film can be formed by adsorbing and aligning iodine on a polyvinyl alcohol film.

[0065] The thickness of the polarizing film is not particularly limited, but is, for example, 1 μm or more and 50 μm or less. The thickness of the polarizing film is preferably 40 μm or less, more preferably 30 μm or less, and further preferably 20 μm or less. On the other hand, the thickness of the polarizing film is preferably 2 μm or more, and more preferably 3 μm or more.

[0066] The polarizing film preferably exhibits absorption dichroism at any wavelength between 380 nm and 780 nm. The orthogonal transmittance (Tc) of the polarizing film is preferably less than 0.5%, more preferably less than 0.1%, and further preferably less than 0.05%. The monomer transmittance (Ts) of the polarizing film is, for example, 41.0% to 45.0%, and preferably greater than 42.0%. The degree of polarization (P) of the polarizing film is, for example, 97.0% to 99.997%, preferably greater than 99.0%, more preferably greater than 99.5%, and further preferably greater than 99.9%.

[0067] The above-mentioned orthogonal transmittance, single transmittance and polarization degree can be measured, for example, using an ultraviolet visible spectrophotometer. The polarization degree P can be measured using an ultraviolet visible spectrophotometer to measure the single transmittance Ts, parallel transmittance Tp and orthogonal transmittance Tc, and the obtained Tp and Tc are obtained by the following formula. It should be noted that Ts, Tp and Tc are Y values ​​measured by a 2-degree viewing field (C light source) of JIS Z 8701 and corrected for visibility.

[0068] Polarization degree P (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0069] As materials for the above-mentioned polyvinyl alcohol-based film, for example, polyvinyl alcohol or its derivatives can be listed. As derivatives of polyvinyl alcohol, for example, polyvinyl formal, polyvinyl acetal; olefins such as ethylene and propylene; substances modified with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, and their alkyl esters, acrylamide, etc. can be listed. The average polymerization degree of polyvinyl alcohol is preferably 100 to 10,000, more preferably 1,000 to 10,000, and further preferably 1,500 to 4,500. The saponification degree of polyvinyl alcohol is preferably 80 mol% to 100 mol%, more preferably 95 mol% to 99.95 mol%. It should be noted that the average polymerization degree and saponification degree can be obtained according to JIS K 6726.

[0070] The polyvinyl alcohol film may contain additives such as plasticizers and surfactants. Examples of plasticizers include polyols such as glycerol, diglycerol, triglycerol, ethylene glycol, propylene glycol, and polyethylene glycol, and condensates thereof. The content of the additives in the polyvinyl alcohol film is preferably 20% by weight or less.

[0071] The iodine content (iodine concentration) of the polarizing film is, for example, not less than 1 wt % and not more than 15 wt %. The iodine content of the polarizing film is preferably not less than 1.5 wt %, more preferably not less than 2 wt %. If it is within this range, the durability can be excellent. For example, fading can be well suppressed. On the other hand, the iodine content of the polarizing film is preferably not more than 12 wt %, more preferably not more than 10 wt %. If it is within this range, for example, polyeneization can be suppressed. It should be noted that the iodine content of the polarizing film refers to the total amount of iodine contained in the polarizing film. Specifically, in the polarizing film, iodine can be present in the form of iodide ions (I - ), iodine molecules (I2), polyiodide ions (I3 - 、I5 - ) etc., but refers to the amount of iodine including all of these forms. The iodine content can be calculated, for example, by a calibration curve method of fluorescent X-ray analysis.

[0072] The polarizing film preferably contains a hindered amine compound. Alternatively, the polarizing film preferably contains a compound having a nitroxyl radical or a nitrooxy group. By including such a compound, for example, a significant decrease in the monomer transmittance and discoloration of the polarizing film in a high temperature environment (for example, above 95°C) can be suppressed. This is believed to be due to the ability to suppress the polyeneization of polyvinyl alcohol in a high temperature environment. Specifically, it is believed to be due to the ability to capture free radicals generated in the polyeneization reaction.

[0073] The molecular weight of the hindered amine compound is preferably 1000 or less, more preferably 500 or less, and further preferably 300 or less. When the polarizing film contains such a compound, for example, a decrease in the single body transmittance of the polarizing film in a high temperature environment can be well suppressed.

[0074] The molecular weight of the compound having a nitroxyl radical or a nitrooxy group is preferably 1000 or less, more preferably 500 or less, and further preferably 300 or less. When the polarizing film contains such a compound, for example, a decrease in the single body transmittance of the polarizing film in a high temperature environment can be well suppressed.

[0075] The hindered amine compound is preferably a water-soluble hindered amine compound that can dissolve at least 1 part by weight in 100 parts by weight of water at 25° C. As the hindered amine compound, it is preferred to use a compound that can dissolve at least 2 parts by weight in 100 parts by weight of water at 25° C., and it is more preferred to use a compound that can dissolve at least 5 parts by weight in 100 parts by weight of water at 25° C. Such a compound can, for example, be efficiently infiltrated into a polarizing film.

[0076] The hindered amine compound may be a secondary or tertiary amine in which an alkyl group is substituted on a carbon adjacent to an amino group to sterically protect the amino group, and examples thereof include compounds having an organic group having the following structure.

[0077] As the compound having a nitroxyl radical or a nitrooxy group, it is preferred to use an N-oxyl compound (having CN(-C)-O as a functional group) from the viewpoint of having a relatively stable radical at room temperature and in the air. · Compound (O · represents an oxygen radical). Examples of the N-oxyl compound include compounds having an organic group having the following structure.

[0078] [Chemical formula 1]

[0079]

[0080] In the general formula (1), R 1 It can also represent oxygen free radicals, R 1It may also represent an oxygen radical, a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 30 carbon atoms, a hydroxyalkyl group, a hydroxyalkoxy group, or an alkoxy group. 2 ~R 5 Each of them independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and n represents 0 or 1. In addition, the left side of the dotted line portion in the general formula (1) represents an arbitrary organic group.

[0081] Examples of the compound having the organic group include compounds represented by the following general formulae (2) to (5).

[0082] [Chemical formula 2]

[0083]

[0084] In the general formula (2), R 1 ~R 5 and n are the same as above, R 6 It represents a hydrogen atom, or an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms.

[0085] [Chemical formula 3]

[0086]

[0087] In the general formula (3), R 1 ~R 5 and n are the same as above, R 7 and R 8 Each of them independently represents a hydrogen atom, or an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms.

[0088] [Chemical formula 4]

[0089]

[0090] In the general formula (4), R 1 ~R 5 and n are the same as above, R 9 ~R 11 Each of them independently represents a hydrogen atom, or an alkyl group, acyl group, amino group, alkoxy group, hydroxyl group or aryl group having 1 to 10 carbon atoms.

[0091] [Chemical formula 5]

[0092]

[0093] In the general formula (5), R 1 ~R 5 and n are the same as above, R 12 It represents a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an amino group, an alkoxy group, a hydroxy group, or an aryl group.

[0094] In the above general formulas (1) to (5), for example, from the viewpoint of effectively suppressing accelerated degradation of polyvinyl alcohol, R 1 Preferably, it is an oxygen radical, a hydrogen atom, a hydroxyl group, or an alkyl group, and more preferably an oxygen radical. In the above general formulas (1) to (5), for example, from the viewpoint of easy availability, R 2 ~R 5 It is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. In the above general formula (2), for example, from the viewpoint of easy availability, R 6 It is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. In the above general formula (3), for example, from the viewpoint of easy availability, R 7 and R 8 Each of R and R is independently preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. 9 ~R 11 It is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. In the above general formula (5), for example, from the viewpoint of easy availability, R 12 In the above-mentioned general formulae (1) to (5), n is preferably 1, for example, from the viewpoint of easy availability.

[0095] The hindered amine compounds include, for example, 2,2,6,6-tetraalkylpiperidine compounds described in columns 5 to 11 of U.S. Patent No. 4,619,956 and columns 3 to 5 of U.S. Patent No. 4,839,405, or acid addition salts thereof or complexes thereof with metal compounds.

[0096] Examples of the N-oxyl compounds include those described in Japanese Unexamined Patent Publication No. 2003-64022, Japanese Unexamined Patent Publication No. 11-222462, Japanese Unexamined Patent Publication No. 2002-284737, and International Publication No. 2016 / 047655. Examples of the compounds having a nitroxyl radical or a nitrooxy group include the following compounds.

[0097] [Chemical formula 6]

[0098]

[0099] In the general formula (6), R represents a hydrogen atom, or an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms.

[0100] [Chemical formula 7]

[0101]

[0102] [Chemical formula 8]

[0103]

[0104] The content of the hindered amine compound in the polarizing film is, for example, 0.005 wt % or more, preferably 0.01 wt % or more, and more preferably 0.02 wt % or more. If it is such a content, for example, the decrease in the monomer transmittance of the polarizing film in a high temperature environment can be well suppressed. On the other hand, the content of the hindered amine compound in the polarizing film is, for example, 20 wt % or less, preferably 15 wt % or less, more preferably 12 wt % or less, and further preferably 10 wt % or less.

[0105] The content of the compound having a nitroxyl radical or a nitrooxy group in the polarizing film is, for example, 0.005% by weight or more, preferably 0.01% by weight or more, and more preferably 0.02% by weight or more. If it is such a content, for example, the decrease in the monomer transmittance of the polarizing film in a high temperature environment can be well suppressed. On the other hand, the content of the compound having a nitroxyl radical or a nitrooxy group in the polarizing film is, for example, 20% by weight or less, preferably 15% by weight or less, more preferably 12% by weight or less, and further preferably 10% by weight or less.

[0106] The polarizing film can be produced by any suitable method. Specifically, the polarizing film can be obtained by subjecting a polyvinyl alcohol film (including a polyvinyl alcohol resin layer provided on a substrate) to various treatments such as dyeing with iodine, stretching, swelling, crosslinking, washing, and drying. Since the various treatments are well known and commonly used in the industry, detailed descriptions thereof are omitted.

[0107] When the polarizing film contains at least one of the above-mentioned hindered amine compound and the above-mentioned compound having a nitroxyl radical or a nitrooxy group (hereinafter, sometimes referred to as a predetermined compound), for example, the predetermined compound is contained in a treatment bath used in at least one of the above-mentioned various treatments. In one embodiment, the predetermined compound is contained in a washing bath of a washing treatment after dyeing treatment, crosslinking treatment, and stretching treatment. According to such a form, the content of the predetermined compound and the content of iodine in the obtained polarizing film can be well adjusted.

[0108] The concentration of the predetermined compound contained in the treatment bath is, for example, 0.01% by weight to 30% by weight, preferably 0.05% by weight to 25% by weight, and more preferably 0.1% by weight to 20% by weight.

[0109] The treatment bath used in the above-mentioned various treatments (e.g., dyeing treatment, stretching treatment, swelling treatment, cross-linking treatment, washing treatment) may also contain additives. Examples of additives include zinc salts, pH adjusters, pH buffers, and other salts. Examples of zinc salts include zinc halides such as zinc chloride and zinc iodide; inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of pH adjusters include strong acids such as hydrochloric acid, sulfuric acid, and nitric acid; and strong bases such as sodium hydroxide and potassium hydroxide. Examples of pH buffers include carboxylic acids such as acetic acid, oxalic acid, and citric acid and their salts, and inorganic weak acids such as phosphoric acid and carbonic acid and their salts. Examples of other salts include chlorides such as sodium chloride, potassium chloride, and barium chloride, nitrates such as sodium nitrate and potassium nitrate, sulfates such as sodium sulfate and potassium sulfate, and salts of alkali metals and alkaline earth metals.

[0110] <Protective layer>

[0111] The protective layer can be composed of any suitable film that can be used as a protective layer of a polarizing film. As the material that is the main component of the film constituting the protective layer, for example, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyether sulfone resins, polysulfone resins, polystyrene resins, cycloolefin resins such as polynorbornene resins, polyolefin resins, (meth) acrylic resins, acetate resins, etc. Here, (meth) acrylic resin refers to acrylic acid and / or methacrylic acid.

[0112] The protective layer (e.g., the second protective layer 22) may be subjected to a surface treatment such as a hard coating treatment as required. Specifically, the protective layer may also be composed of a laminated film having the above-mentioned film as a substrate and a surface treatment layer formed on the substrate. The thickness of the surface treatment layer is preferably 1 μm to 20 μm, more preferably 3 μm to 15 μm, and further preferably 5 μm to 12 μm.

[0113] The thickness of the protective layer can be appropriately set. The thickness of the protective layer is preferably 10 μm to 80 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 50 μm. It should be noted that when the protective layer is subjected to surface treatment, the thickness of the protective layer is the thickness including the thickness of the surface treatment layer.

[0114] In one embodiment, the protective layer (e.g., the first protective layer 21) is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane phase difference Re (550) is 0 nm to 10 nm, and the phase difference Rth (550) in the thickness direction is -10 nm to +10 nm. In another embodiment, the protective layer (e.g., the first protective layer 21) can also function as a phase difference layer.

[0115] <Adhesive Layer>

[0116] The form of the adhesive constituting the adhesive layer is not particularly limited, and for example, a water-based adhesive, a solvent-based adhesive, a hot melt adhesive, an active energy ray-curing adhesive, etc. can be used. Among them, for example, from the aspect of being able to reduce the thickness of the adhesive layer, it is preferred to use a water-based adhesive or an active energy ray-curing adhesive. The thickness of the adhesive layer is preferably 0.01 μm to 5 μm, and more preferably 0.03 μm to 3 μm.

[0117] <Adhesive Layer>

[0118] The above-mentioned adhesive layers can be set to any appropriate thickness. For example, in the first embodiment, the thickness of the first adhesive layer 41 and the second adhesive layer 42 is preferably 1 μm to 50 μm, and more preferably 5 μm to 30 μm. Moreover, the thickness of the third adhesive layer 43 is preferably 20 μm to 500 μm, and more preferably 100 μm to 300 μm. For example, in the second embodiment, the thickness of the first adhesive layer 41 is preferably 1 μm to 50 μm, and more preferably 5 μm to 30 μm. Moreover, the thickness of the second adhesive layer 42 is preferably 20 μm to 500 μm, and more preferably 100 μm to 300 μm.

[0119] The adhesive layer can be composed of any suitable adhesive. As a specific example, the adhesive layer can be composed of an adhesive with polymers such as acrylic acid polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyethers, fluorine-based, rubber-based as base polymers. By adjusting the type, number, combination and proportion of the monomers constituting the base polymer of the adhesive, as well as the amount of cross-linking agent, reaction temperature, reaction time, etc., it is possible to prepare an adhesive with the desired characteristics corresponding to the purpose. The base polymer of the adhesive can be used alone or in combination of two or more. As the base polymer, an acrylic acid polymer is preferably used. Specifically, the adhesive layer is preferably composed of an acrylic acid adhesive.

[0120] The first adhesive layer 41 may be required to have durability (for example, to prevent coloration due to heating). The first adhesive layer 41 is formed of, for example, an adhesive composition containing a (meth)acrylic polymer containing an alkyl (meth)acrylate and a crosslinking agent.

[0121] The (meth)acrylic polymer typically contains an alkyl (meth)acrylate as a main component. In addition, the (meth)acrylate refers to an acrylate and / or a methacrylate.

[0122] As the alkyl group contained in the above-mentioned (meth) alkyl ester, for example, a linear or branched alkyl group having 1 to 18 carbon atoms can be cited. Specific examples of the alkyl group include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, hexyl, cyclohexyl, heptyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecyl, dodecyl, isomyristyl, lauryl, tridecyl, pentadecyl, hexadecyl, heptadecyl, and octadecyl. These can be used alone or in combination. The average carbon number of the alkyl group is preferably 3 to 9.

[0123] The content of the alkyl (meth)acrylate in the (meth)acrylic polymer is, for example, 50 to 95 parts by weight, or preferably 70 to 90 parts by weight, based on 100 parts by weight of the monomer forming the (meth)acrylic polymer.

[0124] As the monomer component constituting the above-mentioned (meth)acrylic acid-based polymer, in addition to the above-mentioned alkyl (meth)acrylate, one or more comonomers selected from the group consisting of aromatic ring-containing (meth)acrylate, amide group-containing monomer, carboxyl group-containing monomer and hydroxyl group-containing monomer can be used. These comonomers can be used alone or in combination.

[0125] The above-mentioned aromatic ring-containing (meth)acrylate is a compound containing an aromatic ring structure in its structure and containing a (meth)acryloyl group. As the aromatic ring of the aromatic ring-containing (meth)acrylate, for example, a benzene ring, a naphthalene ring, and a biphenyl ring can be cited. Specific examples of the aromatic ring-containing (meth)acrylate include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxy (meth)acrylate. (Meth)acrylates having a benzene ring such as 3-phenoxypropyl (meth)acrylate, methoxybenzyl (meth)acrylate, chlorobenzyl (meth)acrylate, toluene (meth)acrylate, and polystyrene (meth)acrylate; (meth)acrylates having a naphthalene ring such as hydroxyethylated β-naphthol acrylate, 2-naphthylethyl (meth)acrylate, 2-naphthyloxyethyl acrylate, and 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate; (meth)acrylates having a biphenyl ring such as biphenyl (meth)acrylate. Among them, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferably used from the viewpoint of improving adhesive properties and durability.

[0126] When an aromatic ring-containing (meth)acrylate is used as the monomer component, the aromatic ring-containing (meth)acrylate is preferably 3% by weight or more, more preferably 8% by weight or more, and even more preferably 12% by weight or more of the total monomer components constituting the (meth)acrylic polymer. The upper limit of the copolymerization amount of the aromatic ring-containing (meth)acrylate is preferably 25% by weight or less, more preferably 22% by weight or less, and even more preferably 20% by weight or less.

[0127] The amide group-containing monomer is a compound containing an amide group in its structure and containing a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the amide group-containing monomer include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylol-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, mercaptoethyl(meth)acrylamide, and other acrylamide monomers; N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, and other N-vinyl-containing lactam monomers. Among these, for example, from the viewpoint of improving durability, it is preferred to use N-vinyl-containing lactam monomers.

[0128] The above-mentioned carboxyl-containing monomer is a compound containing a carboxyl group in its structure and containing polymerizable unsaturated double bonds such as (meth)acryloyl and vinyl. As the carboxyl-containing monomer, for example, (meth)acrylic acid, (meth)carboxyethyl acrylate, (meth)carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid can be listed. Among them, for example, acrylic acid is preferably used from the viewpoint of improving adhesive properties.

[0129] The above-mentioned hydroxyl-containing monomer is a compound containing a hydroxyl group in its structure and containing polymerizable unsaturated double bonds such as (meth)acryloyl and vinyl groups. As hydroxyl-containing monomers, for example, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate and other (meth)acrylate hydroxyalkyl esters; acrylic acid (4-hydroxymethylcyclohexyl)-methyl ester. Among them, for example, from the viewpoint of improving durability, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferably used, and 4-hydroxybutyl (meth)acrylate is more preferably used.

[0130] When a hydroxyl-containing monomer is used as the monomer component, the hydroxyl-containing monomer is preferably 0.01% by weight or more, more preferably 0.03% by weight or more, and further preferably 0.05% by weight or more in the total monomer components constituting the (meth)acrylic polymer. The upper limit of the copolymerization amount of the hydroxyl-containing monomer is preferably 10% by weight or less, more preferably 5% by weight or less, further preferably 2% by weight or less, and particularly preferably 1% by weight or less.

[0131] The weight average molecular weight Mw of the (meth)acrylic acid-based polymer is, for example, 100×10 4 ~300×10 4 , preferably 120×10 4 ~200×10 4 In addition, the weight average molecular weight (Mw) / number average molecular weight (Mn) indicating the molecular weight distribution is preferably 1.8 to 10, more preferably 1.8 to 7, and further preferably 1.8 to 5. It should be noted that the weight average molecular weight and molecular weight distribution (Mw / Mn) are measured by GPC (gel permeation chromatography) and are obtained from values ​​calculated by polystyrene conversion.

[0132] As the crosslinking agent, it is preferred to use an isocyanate crosslinking agent and / or a peroxide crosslinking agent, and it is more preferred to use an isocyanate crosslinking agent and a peroxide crosslinking agent in combination.

[0133] As the isocyanate crosslinking agent, a compound having at least two isocyanate groups (including isocyanate regenerating functional groups in which the isocyanate groups are temporarily protected by a blocking agent or polymerization, etc.) can be used, for example, aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates that can be used in urethanization reactions.

[0134] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate. Examples of the alicyclic polyisocyanate include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate. Examples of the aromatic polyisocyanate include phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.

[0135] In addition, examples of isocyanate crosslinking agents include polymers (dimers, trimers, pentamers, etc.) of the above-mentioned diisocyanates, urethane modified products obtained by reacting with polyols such as trimethylolpropane, urea modified products, biuret modified products, allophanate modified products, isocyanurate modified products, and carbodiimide modified products.

[0136] Examples of commercially available isocyanate crosslinking agents include "Millionate MT", "Millionate MTL", "Millionate MR-200", "Millionate MR-400", "Coronate L", "Coronate HL", "Coronate HX", and "Coronate 2770" manufactured by Tosoh Corporation, and "Takenate D-110N", "Takenate D-120N", "Takenate D-140N", "Takenate D-160N", "Takenate D-165N", "Takenate D-170HN", "Takenate D-178N", "Takenate 500", and "Takenate 600" manufactured by Mitsui Chemicals, Inc.

[0137] In one embodiment, as an isocyanate crosslinking agent, it is preferred to use aromatic polyisocyanates and their modified bodies, i.e., aromatic polyisocyanate compounds, and aliphatic polyisocyanates and their modified bodies, i.e., aliphatic polyisocyanate compounds. Aromatic polyisocyanate compounds can be used with a good balance between crosslinking speed and pot life. As aromatic polyisocyanate compounds, it is particularly preferred to use tolylene diisocyanate and its modified bodies. In another embodiment, as an isocyanate crosslinking agent, a non-aromatic ring system is preferably used. In this specification, "non-aromatic ring system" refers to a compound that does not contain an aromatic ring. Examples of non-aromatic ring isocyanate crosslinking agents are alicyclic isocyanate compounds, aliphatic isocyanate compounds, and their derivatives. Non-aromatic ring isocyanate crosslinking agents may also be aliphatic isocyanate compounds and their derivatives, or may be hexamethylene diisocyanate (HDI) compounds and their derivatives.

[0138] The peroxide crosslinking agent is not particularly limited as long as it is a substance that can generate free radical active species by heating or light irradiation to crosslink the (meth)acrylic polymer. For example, from the viewpoint of workability and stability, it is preferred to use a peroxide crosslinking agent having a 1-minute half-life temperature of 80°C to 160°C, and it is more preferred to use a peroxide crosslinking agent having a 1-minute half-life temperature of 90°C to 140°C.

[0139] The amount of the crosslinking agent is preferably 0.01 to 3 parts by weight, more preferably 0.02 to 2 parts by weight, and further preferably 0.03 to 1 part by weight, relative to 100 parts by weight of the (meth)acrylic polymer. When an isocyanate crosslinking agent is added as the crosslinking agent, the amount thereof is preferably 0.01 to 2 parts by weight, more preferably 0.02 to 1.5 parts by weight, and further preferably 0.03 to 1 part by weight, relative to 100 parts by weight of the (meth)acrylic polymer. It may also be less than 1 part by weight, 0.8 parts by weight or less, or 0.6 parts by weight or less. When a peroxide crosslinking agent is added as the crosslinking agent, the amount thereof is preferably 0.01 to 2 parts by weight, more preferably 0.04 to 1.5 parts by weight, and further preferably 0.05 to 1 part by weight, relative to 100 parts by weight of the (meth)acrylic polymer.

[0140] The adhesive composition may contain a silicon compound. The silicon compound is preferably one or more compounds selected from alkoxysilane compounds and organopolysiloxane compounds having an acidic group or an acid anhydride group derived from an acidic group in the molecule and having no polyether group, and / or a hydrolysis condensate thereof.

[0141] The acidic group is preferably a carboxyl group. The acidic group may also be a group generated by hydrolysis of an acid anhydride group. Specific examples of the acid anhydride group include carboxylic anhydride groups such as succinic anhydride group, phthalic anhydride group, and maleic anhydride group, preferably a succinic anhydride group.

[0142] The alkoxysilane compound specified above is, for example, a compound of the general formula (I): 1 R 2 a Si(OR 3 ) 3-a express.

[0143] In the general formula (I), R 1 is an organic group having 1 to 20 carbon atoms and having an acidic group or an acid anhydride group. The organic group may be linear, branched, or cyclic. 2 are independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom. 3 Each of them independently represents an alkyl group having 1 to 10 carbon atoms, and a is an integer of 0 or 1.

[0144] In the above general formula (I), from the viewpoint of easy availability, R 1 An organic group represented by the following general formula (II) is preferred.

[0145] [Chemical formula 9]

[0146]

[0147] In the general formula (II), A represents a linear or branched alkylene group or alkenylene group having 2 to 10 carbon atoms, and preferably represents a linear or branched alkylene group having 2 to 6 carbon atoms.

[0148] Examples of the alkoxysilane compound specified above include 2-trimethoxysilylethylsuccinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "X-12-967C"), 3-trimethoxysilylpropylsuccinic anhydride, 3-triethoxysilylpropylsuccinic anhydride, 3-methyldiethoxysilylpropylsuccinic anhydride, and 1-carboxy-3-triethoxysilylpropylsuccinic anhydride.

[0149] The organopolysiloxane compound is a compound having a siloxane bond, and includes, for example, a siloxane unit (U1) represented by the following formula (III). The organopolysiloxane compound may further include a siloxane unit (U2) represented by the following formula (IV).

[0150] [Chemical formula 10]

[0151]

[0152] [Chemical formula 11]

[0153]

[0154] In formula (III), X is an organic group having an acidic group or an acid anhydride group, preferably an organic group represented by formula (II). 4 Each of R is independently a hydrogen atom, an alkoxy group having 1 to 10 carbon atoms, or a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom. 4 The alkoxy group of R is preferably a methoxy group or an ethoxy group. 4 The hydrocarbon group is, for example, methyl.

[0155] The number of siloxane units (U1) contained in the organopolysiloxane compound is not particularly limited, and is, for example, 1 to 100, preferably 1 to 50, and more preferably 1 to 20. The number of siloxane units (U2) contained in the organopolysiloxane compound is not particularly limited, and is, for example, 0 to 100, preferably 0 to 50, and more preferably 0 to 20. The organopolysiloxane compound preferably contains at least one siloxane unit (U2).

[0156] The above-mentioned organopolysiloxane compound may also have a structure in which at least one siloxane unit (U1) is inserted between the O-Si bonds contained in the alkoxysilane represented by the following formula (V) or its partial hydrolysis condensate. Both the siloxane unit (U1) and the siloxane unit (U2) may be inserted between the O-Si bonds. Among the multiple O-Si bonds, the siloxane unit (U1) may be inserted between some of the O-Si bonds, and the siloxane unit (U2) may be inserted between the other O-Si bonds.

[0157] R 5 n Si(OR 6 ) 4-n (V)

[0158] In formula (V), R 5 are independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom. 6 Each of them is independently an alkyl group having 1 to 10 carbon atoms. In formula (V), n is 0 or 1.

[0159] Examples of the alkoxysilane represented by formula (V) or its partial hydrolysis condensate include tetramethoxysilane, methyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, and compounds obtained by partial hydrolysis condensation of one or more of these alkoxysilanes.

[0160] The above-mentioned predetermined organopolysiloxane compound can be produced by a known production method described in, for example, JP-A-2013-129809 and JP-A-2013-129691.

[0161] The amount of the silicon compound added is preferably 0.1 part by weight to 3.0 parts by weight, more preferably 0.2 part by weight to 2.0 parts by weight, further preferably 0.2 part by weight to 1.0 part by weight, particularly preferably 0.4 part by weight to 0.6 part by weight, based on 100 parts by weight of the (meth)acrylic polymer.

[0162] The adhesive composition may contain a silane coupling agent containing a reactive functional group. The reactive functional group in the silane coupling agent containing a reactive functional group may be a functional group other than an acid anhydride group. The functional group other than the acid anhydride group is preferably one or more functional groups selected from epoxy, mercapto, amino, isocyanate, isocyanurate, vinyl, styryl, acetoacetyl, urea, thiourea, (meth) acrylic acid and heterocyclic groups.

[0163] Examples of the reactive functional group-containing silane coupling agent include epoxy-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercapto-containing silane coupling agents such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-trimethoxysilane; Silane coupling agents containing amino groups such as ethoxysilyl-N-(1,3-dimethylbutylene)propylamine and N-phenyl-γ-aminopropyltrimethoxysilane; silane coupling agents containing isocyanate groups such as 3-isocyanatepropyltriethoxysilane; silane coupling agents containing vinyl groups such as vinyltrimethoxysilane and vinyltriethoxysilane; silane coupling agents containing styrene groups such as p-styryltrimethoxysilane; silane coupling agents containing (meth) acrylic groups such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane. Among them, epoxy group-containing silane coupling agents and mercapto group-containing silane coupling agents are preferred.

[0164] As a silane coupling agent containing a reactive functional group, an oligomer silane coupling agent having a plurality of alkoxysilyl groups in the molecule can also be used. Specific examples include epoxy-containing oligomer silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd., trade names "X-41-1053", "X-41-1059A", "X-41-1056", and "X-40-2651"; and mercapto-containing oligomer silane coupling agents "X-41-1818", "X-41-1810", and "X-41-1805". Since oligomer silane coupling agents are not easily volatile and have a plurality of alkoxysilyl groups, they are effective in improving durability.

[0165] When a reactive functional group-containing silane coupling agent is added to the adhesive composition, the amount of the reactive functional group-containing silane coupling agent is preferably 0.001 parts by weight or more and 5 parts by weight or less, more preferably 0.01 parts by weight or more and 1 part by weight or less, and further preferably 0.05 parts by weight or more and 0.6 parts by weight or less, relative to 100 parts by weight of the (meth)acrylic polymer. In addition, for example, from the viewpoint of improving durability, the weight ratio of the silicon compound to the reactive functional group-containing silane coupling agent (the amount of the silicon compound added / the amount of the reactive functional group-containing silane coupling agent added) is preferably 0.1 or more and 50 or less, more preferably 0.5 or more and 15 or less, and further preferably 1 or more and 5 or less.

[0166] The above-mentioned adhesive composition may contain a conductive agent. As the conductive agent, any suitable conductive agent may be used. As the conductive agent, an organic cationic conductive agent is preferably used. The organic cationic conductive agent may be representatively an organic cationic salt. The cationic portion (cationic component) of the organic cationic salt may have an organic structure. The anionic portion (anionic component) of the organic cationic salt may have an organic structure or an inorganic structure. The organic cationic salt may also be an ionic solid having a melting point of 40° C. or above.

[0167] Examples of the above-mentioned cations are organic oniums containing organic groups. Examples of oniums contained in organic oniums are nitrogen-containing oniums, sulfur-containing oniums, and phosphoniums, preferably nitrogen-containing oniums and sulfur-containing oniums. Examples of nitrogen-containing oniums are ammonium cations, piperidinium cations, pyrrolidinium cations, pyridinium cations, cations having a pyrroline skeleton, cations having a pyrrole skeleton, imidazolium cations, tetrahydropyrimidinium cations, dihydropyrimidinium cations, pyrazolium cations, and pyrazolinium cations. Examples of sulfur-containing oniums are sulfonium cations. Examples of phosphonium-containing oniums are phosphonium cations. Examples of organic groups contained in organic oniums are alkyls, alkoxys, and alkenyls. Specific examples of preferred organic oniums are tetraalkylammonium cations (e.g., tributylmethylammonium cations), alkylpiperidinium cations, and alkylpyrrolidinium cations.

[0168] An example of the above anion is Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、ClO4 - 、NO3 - 、CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(CN)2N - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - and anions represented by the following general formulae (a) to (d).

[0169] (a)(C n F 2n+1 SO2)2N - (n is an integer from 1 to 10)

[0170] (b)CF2(C m F 2m SO2)2N - (m is an integer from 1 to 10)

[0171] (c) - O3S(CF2) l SO3 - (l is an integer from 1 to 10)

[0172] (d)(C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (p and q are independently an integer of 1 to 10)

[0173] Specific examples of the organic cationic conductive agent include 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) and trimethylbutylammonium bis(trifluoromethanesulfonyl)imide.

[0174] The amount of the organic cationic conductive agent to be added is, for example, 0.1 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 0.7 parts by weight or more, 0.9 parts by weight or more, 1 part by weight or more, 3 parts by weight or more, 5 parts by weight or more, or 7 parts by weight or more, based on 100 parts by weight of the (meth)acrylic polymer. The upper limit of the amount to be added is, for example, 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, 10 parts by weight or less, 8 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, or 1.5 parts by weight or less, based on 100 parts by weight of the (meth)acrylic polymer.

[0175] <Support>

[0176] The support is provided adjacent to an adhesive layer that can function as a light diffusion layer, for example. As a support, a support having suitable mechanical strength is used. As such a support, for example, a film (laminated film) having the hard coating layer is used. The thickness of the hard coating layer is preferably 1 μm to 20 μm, more preferably 3 μm to 15 μm, and further preferably 5 μm to 12 μm. As the material that is the main component of the film constituting the support, for example, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyether sulfone resins, polysulfone resins, polystyrene resins, cycloolefin resins such as polynorbornene, polyolefin resins, (meth) acrylic resins, acetate resins, etc. can be cited. The thickness of the support (film having the hard coating layer) is preferably 10 μm to 80 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 50 μm.

[0177] [Display device]

[0178] The optical layered body can be used for a display device, and a display device according to an embodiment of the present invention includes the optical layered body. Figure 3 1 is a schematic cross-sectional view schematically showing a liquid crystal display device according to an embodiment of the present invention. Specifically, it is a schematic cross-sectional view showing a display panel portion included in a liquid crystal display device according to an embodiment of the present invention.

[0179] The panel unit 1 of the liquid crystal display device includes a first display panel 100, a second display panel 200 disposed at a position closer to the observer than the first display panel 100, an optical laminate 60 disposed between the first display panel 100 and the second display panel 200, and a backlight 300 for irradiating light from the back side to the plurality of display panels. The optical laminate 60 is attached to the first display panel 100 via a first adhesive layer 41, and is attached to the second display panel 200 via a third adhesive layer 43. Figure 3In the figure, the upper side is the observer side. Although not shown in the figure, a transparent plate may be provided on the observer side of the first display panel 100 .

[0180] The first display panel 100 includes a first liquid crystal unit 101 and a first polarizing plate 102 disposed on the backlight 300 side of the first liquid crystal unit 101. The second display panel 200 includes a second liquid crystal unit 201 and a second polarizing plate 202 disposed on the observer side of the second liquid crystal unit 201. The first liquid crystal unit 101 and the second liquid crystal unit 201 respectively include a thin film transistor substrate (TFT substrate) not shown, a color filter substrate (CF substrate) and a liquid crystal layer disposed between the TFT substrate and the CF substrate. As a driving method of the first liquid crystal unit 101 and the second liquid crystal unit 201, any appropriate driving method can be adopted.

[0181] As described above, since the optical laminate 60 may include a light diffusion layer, the liquid crystal display device of this embodiment can suppress the generation of moire fringes, for example, the generation of moire fringes caused by the pattern of the black matrix of the CF substrate between the first liquid crystal unit 101 and the second liquid crystal unit 201.

[0182] For example, if the polarizer 30 is exposed to a high temperature environment in a state where moisture exists in it, the acid present in the adhesive layer can migrate to the polarizing film 10, and can act as an acid catalyst for the polyeneization of the polarizing film 10 caused by the dehydration of polyvinyl alcohol. It is believed that in the structure in which the display panels 100 and 200 are arranged on both sides of the polarizer 30, the moisture in the polarizer 30 is not easy to escape, and polyeneization is easily promoted. Even in such an environment that easily promotes polyeneization, polyeneization can be suppressed by making a predetermined compound exist in the polarizing film 10. As a result, it is believed that the reduction in the monomer transmittance of the polarizing film 10 can be suppressed. It should be noted that the thicker the adhesive layer, the greater the influence of the acid present in the adhesive layer.

[0183] In the optical laminate 60, the first adhesive layer 41 attached to the first display panel 100 disposed on the backlight 300 side is easily affected by the heat and / or light of the backlight 300. Moreover, in the configuration in which the display panels 100 and 200 are disposed on both sides of the optical laminate 60, free radicals are easily generated at the end of the end surface of the first adhesive layer 41 in contact with air (oxygen), and yellowing may occur, for example. By forming the first adhesive layer 41 that is easily affected by the heat and / or light of the backlight 300 from the above-mentioned adhesive composition, for example, the occurrence of the above-mentioned yellowing can be suppressed.

[0184] In one embodiment, the first adhesive layer 41 that is easily affected by the backlight 300 does not substantially contain fine particles. According to such an aspect, the first adhesive layer 41 can have excellent adhesive properties with respect to the first display panel 100 .

[0185] Since the optical laminate 60 has an adhesive layer with high haze (e.g., haze of 66% or more), the light amount of the backlight source 300 can be increased from the viewpoint of ensuring brightness. In this case, the polarizer 30 and / or the first adhesive layer 41 are further affected by the heat and / or light of the backlight source 300, and the above-mentioned polyeneization and / or yellowing problems are likely to occur.

[0186] Example

[0187] The present invention will be specifically described below by way of examples, but the present invention is not limited to these examples. It should be noted that thickness, haze, iodine concentration and weight-average molecular weight (Mw) are values ​​measured by the following measuring methods. In addition, unless otherwise specified, "parts" and "%" are weight references.

[0188] <Thickness>

[0189] The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL Ltd., product name “JSM-7100F”). The thickness exceeding 10 μm was measured using a digital micrometer (manufactured by ANRITSU, product name “KC-351C”).

[0190] <Haze>

[0191] The haze was measured in accordance with JIS K 7136 using a haze meter (manufactured by Murakami Color Science Laboratory, product name “HN-150”).

[0192] <Iodine concentration>

[0193] The polarizing film was measured using a fluorescent X-ray analyzer (Rigaku Corporation, "ZSX-PRIMUSIV") with a measurement diameter of φ20 mm, and the iodine concentration (weight %) was determined using the following formula. It should be noted that the following coefficients when calculating the iodine concentration vary, for example, depending on the measuring device, but can be determined using an appropriate calibration curve.

[0194] Iodine concentration (weight %) = 14.474 × (fluorescent X-ray intensity) / (film thickness) (kcps / μm)

[0195] <Weight average molecular weight (Mw)>

[0196] The weight average molecular weight (Mw) is measured by GPC (gel permeation chromatography). Mw / Mn is measured in the same manner.

[0197] Analytical device: HLC-8120GPC manufactured by Tosoh Corporation

[0198] Column: Made by Tosoh Corporation, G7000H XL +GMH XL +GMH XL

[0199] · Pillar size: 7.8mmφ×30cm each, total 90cm

[0200] Column temperature: 40°C

[0201] Flow rate: 0.8mL / min

[0202] Injection volume: 100μL

[0203] ·Eluent: Tetrahydrofuran

[0204] Detector: Differential Refractometer (RI)

[0205] Standard sample: polystyrene

[0206] [Example 1]

[0207] (Production of Polarizing Film 1)

[0208] A polyvinyl alcohol film having an average degree of polymerization of 2400, a degree of saponification of 99.9 mol %, and a thickness of 45 μm was prepared.

[0209] A polyvinyl alcohol film is immersed in a swelling bath (water bath) at 20°C between rollers having different peripheral speed ratios for 30 seconds to swell and is stretched to 2.2 times in the conveying direction (swelling process). Subsequently, the film is immersed in a dyeing bath at 30°C (an iodine aqueous solution obtained by combining iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) for 30 seconds to dye the film while adjusting the iodine concentration of the final polarizing film to 4.47 weight% and stretching it to 3.3 times in the conveying direction based on the original polyvinyl alcohol film (the polyvinyl alcohol film that has not been stretched at all in the conveying direction) (dyeing process).

[0210] Next, the dyed polyvinyl alcohol film was immersed in a crosslinking bath (aqueous solution with a boric acid concentration of 3.0 wt % and a potassium iodide concentration of 3.0 wt %) at 40° C. for 28 seconds and stretched 3.6 times in the conveying direction based on the original polyvinyl alcohol film (crosslinking step).

[0211] Furthermore, the obtained polyvinyl alcohol film is immersed in a stretching bath at 61°C (an aqueous solution having a boric acid concentration of 4.0% by weight and a potassium iodide concentration of 5.0% by weight) for 60 seconds and stretched to 6.0 times along the conveying direction based on the original polyvinyl alcohol film (stretching process), and then immersed in a washing bath at 35°C (an aqueous solution having a potassium iodide concentration of 2.0% by weight and a concentration of 0.4% by weight of the compound represented by the following general formula (9)) for 10 seconds (washing process). The washed polyvinyl alcohol film is dried at 40°C for 30 seconds to produce a polarizing film having a thickness of 18 μm and an iodine concentration of 4.47% by weight. It should be noted that the compound represented by the following general formula (9) is a compound that dissolves more than 1 part by weight per 100 parts by weight of water at 25°C.

[0212] About 20 mg of the obtained polarizing film was collected and quantified. After being heated and dissolved in 1 mL of water, it was diluted with 4.5 mL of methanol. The obtained extract was filtered with a membrane filter and the filtrate was measured using HPLC (Waters, "ACQUITYUPLC H-class Bio") to determine the content of the compound represented by the following general formula (9) in the polarizing film. The result was 0.28 weight %.

[0213] [Chemical formula 12]

[0214]

[0215] (Production of polarizing film)

[0216] An acrylic film having a thickness of 30 μm and made of an acrylic polymer having a lactone ring structure was bonded to one surface (first main surface) of the polarizing film using a polyvinyl alcohol-based adhesive.

[0217] Next, a 49 μm thick HC-TAC film was bonded to the other side (second main surface) of the polarizing film using a polyvinyl alcohol-based adhesive. It should be noted that the 49 μm thick HC-TAC film is a laminated film in which a 9 μm thick hard coating (HC) layer (manufactured by Konica Minolta, "KC4UY") is formed on a 40 μm thick triacetylcellulose (TAC) film, and the laminated film is bonded in such a way that the TAC film of the laminated film becomes the polarizing film side to obtain a laminated product.

[0218] The obtained laminate was heated and dried in an oven set at 70° C. for 5 minutes to produce a polarizing plate.

[0219] (Preparation of Acrylic Adhesive Composition 1)

[0220] A monomer mixture containing 76.9 parts by weight of butyl acrylate, 18 parts by weight of benzyl acrylate, 5 parts by weight of acrylic acid and 0.1 parts by weight of 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a cooler. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts by weight of ethyl acetate to 100 parts by weight of the monomer mixture (solid content), and nitrogen gas was introduced while slowly stirring to replace the inside of the flask with nitrogen. Then, a polymerization reaction was performed for 8 hours while the liquid temperature in the flask was maintained at 55°C to prepare a solution of an acrylic polymer having a weight average molecular weight (Mw) of 1.95 million and Mw / Mn=3.9.

[0221] An isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, manufactured by Tosoh Corporation, “Coronate L”) 0.4 part by weight, a peroxide crosslinking agent (manufactured by NOF Corporation, “NYPER BMT”) 0.1 part by weight, a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., “X-41-1056”) 0.2 part by weight, and 0.6 part by weight of the following organopolysiloxane compound were added to 100 parts by weight of the solid content of the obtained acrylic polymer solution to prepare an acrylic adhesive composition 1.

[0222] (Preparation of organopolysiloxane compound)

[0223] An organopolysiloxane compound was prepared according to the method described in Example 1 of Japanese Patent Application Publication No. 2013-129809. The organopolysiloxane compound comprises the above-mentioned siloxane units (U1) and (U2). In the siloxane unit (U1), X is a propyl succinic anhydride group, and R 4 In the siloxane unit (U2), two R 4 The content of the siloxane unit (U1) in the produced organopolysiloxane compound was 27 mol%, and the content of the siloxane unit (U2) was 73 mol%. The weight average molecular weight was about 1,000.

[0224] (Formation of First Adhesive Layer)

[0225] The acrylic adhesive composition 1 was applied onto a release liner (polyethylene terephthalate film treated with a silicone release agent, 38 μm thick, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., “MRF38”) so that the thickness of the adhesive layer after drying would be 20 μm, and dried at 155° C. for 1 minute to form a first adhesive layer on the release liner.

[0226] (Preparation of Polarizing Plate with Adhesive Layer)

[0227] The first pressure-sensitive adhesive layer was bonded to the acrylic film-side surface of the polarizing plate to obtain a pressure-sensitive adhesive layer-attached polarizing plate.

[0228] (Preparation of Light Diffusing Layer Forming Composition)

[0229] 100 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of hydroxyethyl acrylate were solution polymerized to obtain an acrylic polymer having a weight average molecular weight (Mw) of 2,000,000.

[0230] 100 parts by weight of the obtained acrylic polymer, 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, manufactured by Tosoh Corporation, “Coronate L”), 0.1 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Silicone, “KBM403”), and 7 parts by weight of spherical fine particles (silicone resin having a refractive index of 1.42 and an average particle size of 4.5 μm, manufactured by Momentive Performance Materials Japan, “Tospearl 145”) were added to toluene so that the solid content became 10% by weight, and the mixture was stirred for 15 minutes with a disperser to disperse the fine particles, thereby preparing a light diffusion layer forming composition.

[0231] (Formation of Second Adhesive Layer)

[0232] The obtained light diffusion layer forming composition was applied to the surface of the polarizer side of the polarizer with an adhesive layer using a wire bar so that the thickness after drying was 23 μm and dried to form a second adhesive layer having a haze of 85%.

[0233] (Production of optical laminate)

[0234] Next, a 49 μm thick HC-TAC film was bonded onto the second pressure-sensitive adhesive layer of the pressure-sensitive adhesive layer-attached polarizing plate, and a 250 μm thick pressure-sensitive adhesive layer was further formed on the surface of the HC-TAC film to produce an optical laminate.

[0235] [Example 2]

[0236] An optical laminate was produced in the same manner as in Example 1 except that the amount of spherical fine particles in the preparation of the light diffusion layer forming composition was 5 parts by weight and the second pressure-sensitive adhesive layer had a haze of 80%.

[0237] [Example 3]

[0238] An optical layered body was produced in the same manner as in Example 1 except that the amount of spherical fine particles in the preparation of the light diffusion layer forming composition was 4 parts by weight and the second pressure-sensitive adhesive layer had a haze of 75%.

[0239] [Example 4]

[0240] An optical laminate was produced in the same manner as in Example 1 except that the first pressure-sensitive adhesive layer was formed using the acrylic pressure-sensitive adhesive composition 2 described below.

[0241] (Preparation of Acrylic Adhesive Composition 2)

[0242] A monomer mixture containing 77.95 parts by weight of butyl acrylate, 16 parts by weight of phenoxyethyl acrylate, 3 parts by weight of acrylic acid, 1 part by weight of N-vinyl-2-pyrrolidone and 0.05 parts by weight of 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a cooler. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added to 100 parts by weight of the monomer mixture together with 100 parts by weight of ethyl acetate, and nitrogen gas was introduced while slowly stirring to replace the inside of the flask with nitrogen. Then, the liquid temperature in the flask was maintained at 55° C. and a polymerization reaction was performed for 6 hours to prepare a solution of an acrylic polymer having a weight average molecular weight (Mw) of 2.5 million and Mw / Mn=3.0.

[0243] Acrylic adhesive composition 2 was prepared by adding 0.5 parts by weight of a non-aromatic isocyanate crosslinking agent (an allophanate obtained by addition reaction of hexamethylene diisocyanate and acrylic polyol, manufactured by Tosoh Corporation, “Coronate 2770”), 0.2 parts by weight of a peroxide crosslinking agent (manufactured by NOF Corporation, “NYPER BMT”), and 1 part by weight of 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) to 100 parts by weight of the solid content of the obtained acrylic polymer solution.

[0244] [Example 5]

[0245] An optical laminate was produced in the same manner as in Example 2, except that the acrylic pressure-sensitive adhesive composition 2 was used to form the first pressure-sensitive adhesive layer.

[0246] [Example 6]

[0247] An optical laminate was produced in the same manner as in Example 3 except that the acrylic pressure-sensitive adhesive composition 2 was used to form the first pressure-sensitive adhesive layer.

[0248] [Example 7]

[0249] An optical laminate was produced in the same manner as in Example 2 except that the first pressure-sensitive adhesive layer was formed using the acrylic pressure-sensitive adhesive composition 3 described below.

[0250] (Preparation of Acrylic Adhesive Composition 3)

[0251] A monomer mixture containing 77.95 parts by weight of butyl acrylate, 16 parts by weight of phenoxyethyl acrylate, 3 parts by weight of acrylic acid, 1 part by weight of N-vinyl-2-pyrrolidone and 0.05 parts by weight of 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a cooler. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added to 100 parts by weight of the monomer mixture together with 100 parts by weight of ethyl acetate, and nitrogen gas was introduced while slowly stirring to replace the inside of the flask with nitrogen. Then, the liquid temperature in the flask was maintained at 55° C. and a polymerization reaction was performed for 6 hours to prepare a solution of an acrylic polymer having a weight average molecular weight (Mw) of 2.5 million and Mw / Mn=3.0.

[0252] Acrylic adhesive composition 3 was prepared by mixing 100 parts by weight of the solid content of the obtained acrylic polymer solution with 1 part by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, manufactured by Tosoh Corporation, “Coronate L”), 0.2 parts by weight of a peroxide crosslinking agent (manufactured by NOF Corporation, “NYPER BMT”), 0.5 parts by weight of lithium bis(trifluoromethanesulfonyl)imide, 0.05 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., “X-41-1056”), 0.4 parts by weight of a polyether compound (manufactured by Kaneka Corporation, “SILYL SAT10”), and 0.4 parts by weight of the above-mentioned organopolysiloxane compound.

[0253] [Comparative Example 1]

[0254] An optical layered body was produced in the same manner as in Example 1 except that the amount of spherical fine particles in the preparation of the light diffusion layer forming composition was 2 parts by weight and the second pressure-sensitive adhesive layer had a haze of 55%.

[0255] [Comparative Example 2]

[0256] An optical layered body was produced in the same manner as in Example 2, except that the polarizing film 2 described below was used to produce a polarizing plate.

[0257] (Production of Polarizing Film 2)

[0258] A polyvinyl alcohol film having an average degree of polymerization of 2400, a degree of saponification of 99.9 mol %, and a thickness of 45 μm was prepared.

[0259] A polyvinyl alcohol film is immersed in a swelling bath (water bath) at 28°C between rollers having different peripheral speed ratios for 30 seconds to swell and is stretched to 2.4 times in the conveying direction (swelling process). Subsequently, the film is immersed in a dyeing bath at 25°C (an aqueous solution having an iodine concentration of 0.03 wt % and a potassium iodide concentration of 0.3 wt %) for 45 seconds to be dyed and is stretched to 3.7 times in the conveying direction based on the original polyvinyl alcohol film (a polyvinyl alcohol film that has not been stretched at all in the conveying direction) (dyeing process).

[0260] Next, the dyed polyvinyl alcohol film was immersed in a cross-linking bath (an aqueous solution of 3.0 wt% boric acid, 3.0 wt% potassium iodide, and 3.6 wt% zinc sulfate (1.5 wt% zinc ion concentration)) at 40°C for 20 seconds and stretched to 4.2 times along the conveying direction based on the original polyvinyl alcohol film (cross-linking process).

[0261] Next, the obtained polyvinyl alcohol film is immersed in a stretching bath (an aqueous solution having a boric acid concentration of 4.0 wt%, a potassium iodide concentration of 5.0 wt%, and a zinc sulfate concentration of 5.0 wt% (a zinc ion concentration of 2.0 wt%)) at 65°C for 50 seconds and stretched to 6.0 times along the conveying direction based on the original polyvinyl alcohol film (stretching process), and then immersed in a washing bath (an aqueous solution having a potassium iodide concentration of 2.5 wt%) at 27°C for 5 seconds (washing process).

[0262] The washed polyvinyl alcohol film was dried at 25° C. for 2 minutes to prepare a polarizing film having a thickness of 18 μm.

[0263] [Comparative Example 3]

[0264] An optical layered body was produced in the same manner as in Example 5, except that the polarizing film 2 was used to produce a polarizing plate.

[0265] The following evaluations were performed on the Examples and Comparative Examples. The evaluation results are summarized in Table 1.

[0266] <Evaluation>

[0267] 1. Moire fringes

[0268] Prepare the IPS (In Plane Switching) panel (first liquid crystal display panel, second liquid crystal display panel) and backlight for vehicle use. Figure 3 As shown in the figure, after the first adhesive layer of the obtained optical laminate is attached to the liquid crystal unit of the first liquid crystal display panel, and the adhesive layer with a thickness of 250 μm of the optical laminate is attached to the liquid crystal unit of the second liquid crystal display panel, the backlight source is lit from the first liquid crystal display panel side, and the presence or absence of the moire fringe phenomenon (the occurrence of rainbow spots) is confirmed by visual observation from the second liquid crystal display panel side.

[0269] (Evaluation Criteria)

[0270] Good: No moire (rainbow spots) can be detected

[0271] Bad: Moire fringes (rainbow spots) are observed

[0272] 2. Appearance 1

[0273] A non-alkali glass plate 1 with a thickness of 0.7 mm was attached to the adhesive layer with a thickness of 250 μm of the optical laminate. Thereafter, the release liner used in forming the first adhesive layer was peeled off from the first adhesive layer, and a non-alkali glass plate 2 with a thickness of 0.7 mm was attached to the peeled surface to obtain an evaluation sample. After the evaluation sample was left in an environment at a temperature of 95° C. for 1000 hours, the appearance of the heated optical laminate was visually observed under fluorescent light irradiation.

[0274] (Evaluation Criteria)

[0275] Good: No significant change was observed in the appearance of the optical layered body compared to a separately prepared evaluation sample (not left in an environment with a temperature of 95°C)

[0276] Bad: A significant color change (discoloration to brown or black) was observed in the appearance of the optical layered body compared to a separately prepared evaluation sample (not left in an environment with a temperature of 95° C.)

[0277] 3. Appearance 2

[0278] The evaluation sample was placed in a heated atmosphere at a temperature of 95° C. for 500 hours. After placement, the evaluation sample was irradiated with light from the glass plate 2 side of the evaluation sample, and the appearance of the optical laminate after irradiation was observed visually. It should be noted that for the evaluation, a backlight having a light emitting area capable of irradiating light at a luminous intensity of 15000 candela was used, which was equivalent to the CIE standard light source D65.

[0279] (Evaluation Criteria)

[0280] Good: No change was observed in the appearance of the optical layered body

[0281] Bad: There is no change in the appearance of the optical laminate, but the edge of the end surface including the pressure-sensitive adhesive layer is colored (yellowing)

[0282] Table 1

[0283] Moire fringes Appearance 1 Appearance 2 Example 1 good good good Example 2 good good good Example 3 good good good Example 4 good good good Example 5 good good good Example 6 good good good Example 7 good good bad Comparative Example 1 bad good good Comparative Example 2 good bad good Comparative Example 3 good bad good Reference Example 1 good good good Reference Example 2 good good good Reference Example 3 good good good

[0284] In Comparative Examples 2 and 3, discoloration was observed in the center of the display panel. In Example 7, yellowing was observed in the edge of the first pressure-sensitive adhesive layer.

[0285] It should be noted that, for Reference Examples 1 and 2 in Table 1, the samples for evaluation were prepared in the same manner as above, and subjected to the above evaluation, except that the alkali-free glass plate 1 was not bonded to the optical laminates of Comparative Examples 2 and 3, respectively. In addition, for Reference Example 3 in Table 1, the samples for evaluation were prepared in the same manner as above, and subjected to the above evaluation, except that the alkali-free glass plate 1 was not bonded to the optical laminate of Example 7.

[0286] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the configuration shown in the above-described embodiment may be replaced with a configuration that is substantially the same as the configuration shown in the above-described embodiment, a configuration that exhibits the same function and effect, or a configuration that can achieve the same purpose.

[0287] Industrial Applicability

[0288] The optical laminate according to the embodiment of the present invention can be suitably used in a display device including, for example, a plurality of display panels stacked on top of each other.

Claims

1. An optical laminate comprising: A polarizing plate including a polarizing film having a first major surface and a second major surface facing each other; a first adhesive layer disposed on the first main surface side of the polarizing film; and a second adhesive layer disposed on the second main surface side of the polarizing film, The haze of at least one of the first adhesive layer and the second adhesive layer is 66% or more, The polarizing film is composed of a polyvinyl alcohol-based film containing iodine and contains a compound having a nitroxyl radical or a nitrooxy group.

2. The optical layered body according to claim 1, wherein: The second adhesive layer has a haze of 66% or more. 3 . The optical laminate according to claim 2 , further comprising a third pressure-sensitive adhesive layer disposed on the second main surface side of the polarizing film. 4 . The optical laminate according to claim 2 , further comprising a support disposed on the second main surface side of the polarizing film.

5. The optical layered body according to claim 1, wherein: The polarizing film contains the compound having a nitroxyl radical or a nitrooxy group in an amount of 20 wt % or less.

6. The optical layered body according to claim 1, wherein: The polarizing film has an iodine content of 1% by weight or more and 15% by weight or less.

7. The optical layered body according to claim 1, wherein: The first adhesive layer is formed of an adhesive composition comprising a (meth)acrylic polymer and a cross-linking agent. The cross-linking agent comprises an isocyanate cross-linking agent, The content of the isocyanate crosslinking agent is less than 1 part by weight based on 100 parts by weight of the (meth)acrylic polymer.

8. The optical layered body according to claim 7, wherein: The isocyanate cross-linking agent is a non-aromatic ring system.

9. A display device comprising a plurality of display panels including a liquid crystal unit and arranged in a stacked manner, wherein an image is displayed on each of the display panels, comprising: 1st display panel; a second display panel disposed at a position closer to the observer than the first display panel; and The optical laminate according to any one of claims 1 to 8 disposed between the first display panel and the second display panel, The first pressure-sensitive adhesive layer of the optical laminate is bonded to the first display panel.

Citation Information

Patent Citations

  • Production of high-purity (Meth)Acrylic acid ester

    JP1999222462A

  • Method for diminishing n-oxyl compound

    JP2002284737A

  • Method of producing polyfunctional vinyl compound

    JP2003064022A

  • Liquid crystal display device and television receiver

    JP2007310161A

  • Acid anhydride group-containing organosiloxane and method for producing the same

    JP2013129691A